Effectiveness and Spatial Distribution of Wastewater Land Application Technical Approval in East Java - Hakasmanti, Erika; Semedi, Bambang; Hardjoko, Arief Tri; Koentjoro, Maharani Pertiwi; Supriyadi, Supriyadi (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
The management of industrial wastewater presents a considerable challenge to governments globally, mainly because of the difficulties faced in ensuring that regulatory frameworks are properly instituted. This study evaluated the success of the technical approval for using wastewater" regulatory framework and its geographic spread across East Java. This was evaluated using data from 35 business participants from 16 different districts/cities via a combination of quantitative (survey) and qualitative (spatial analysis) methods. The overall effectiveness of the regulatory framework was rated high (84.69%), with the dimension "Regulatory Appropriateness" rated the highest (85.57%), while the dimension "Environmental Appropriateness" ranked the lowest (84.14%). From the geographic analysis, it was evident that cities and industrial centers dominated the level of support, with many non-industrial areas displaying very little engagement. Collectively, these results demonstrate the need for policies to be designed with a geographic perspective and for sufficient institutional support to be targeted towards non-urban areas. This will allow stakeholders to provide the required technical support, increase the utilization of technology to enhance service delivery, and engage the local workforce to the greatest degree possible to enable sustainable and equitable environmental governance.